Environmental discourses in public and international law - Jessup, Brad 1978-; Rubenstein, Kim (Cambridge, UK New York Cambridge University Press, 2012)
"This collection of essays examines the development and application of environmental laws and the relationship between public laws and international law. Notions of good governance, transparency and fairness in decision-making are analysed within the area of the law perceived as having the greatest potential to address today's global environmental concerns. International trends, such as free trade and environmental markets, are also observed to be infiltrating national laws. Together, the essays illustrate the idea that in the context of environmental problems being dynamic and environmental changes appearing suddenly, laws become difficult to design and effect. Typically, they are also devised within a conflicted setting. It is in this changeable and discordant context that environmental discourses such as precaution, justice, risk, equity, security, citizenship and markets contribute to legal responses, present legal opportunities or hinder progress"-- Provided by publisher.
"The world is talking, pondering, and strategising about the environment. Ever more of the environment has been identified, publicly contemplated, or designated for despoliation and resource extraction. Remote and 'wild' places like the rugged Australian Kimberley and the far reaches of North America are now subject to advanced plans for fossil fuel extraction. Environmental disasters, including fires, floods, cyclones, earthquakes and tsunami, and schemes to alleviate or prevent future human suffering from catastrophe, have occupied governmental and organisational attention. Meanwhile, concerns about environmental degradation, and in particular human-induced climate change, dominate Western media and national and international politics, and are connecting communities through conversation and localised action. The nature, breadth and extent of global responses to climate change are also points of contention between the developing and developed worlds"-- Provided by publisher.
Part IV. Discourses in Climate Law -- Climate change : limits discourses at the interface of international law and environmental law / Lee Godden -- The national interest or good international citizenship? Australia and its approach to international and public climate law / River Cordes-Holland -- The Asia-Pacific partnership : a deepened market liberal model for the international climate regime? / Jeffrey Mcgee and Ros Taplin -- Global gazing : viewing markets through the lens of emissions trading discourses / Sanja Bogojevic -- Part V. Discourses in the Commons -- Polar opposites : environmental discourses and management in Antarctica and the Arctic / Donald R. Rothwell -- Heritage discourses / Ben Boer and Stefan Gruber -- Environmental principles and social change in the ocean dumping regime : a case study of the disposal of carbon dioxide into the seabed / Afshin Akhtarkhavari -- Environmental discourses in the ocean commons : the case of ocean fertilisation / Julia Mayo-Ramsay -- Concluding remarks : discourse versus strategy / Thomas Pogge.
Keywords: Environmental law, International -- Congresses; Electronic books